Business case for mussel aquaculture in offshore wind farms in the North Sea. (November 2017) - van den Burg, S.W.K.; Kamermans, P.; Blanch, M.; Pletsas, D.; Poelman, M.; Soma, K.; Dalton, G.
Abstract: The European Blue Growth strategy aims to expand the new maritime sectors of aquaculture, energy, biotechnology, coastal tourism and mineral mining. Growth of these sectors will increases pressure on the seas, particularly on those areas that are densely used by traditional sectors such as fisheries and transport. This has triggered interest in developing multiuse of space and multiuse platforms at sea. This paper assesses the feasibility of offshore mussel production project in wind farms by design and ex-ante evaluation of a mussel aquaculture system in the North Sea. A system for mussel cultivation in the Dutch Borssele offshore wind farm was designed, producing both mussel seed and consumption-sized mussels with semi-submerged longlines. Based on the economic model and the risk assessment, this paper concludes that mussel aquaculture is an appealing commercial model for increased returns in offshore wind farms. The economic models shows that the internal rate of return and net present value are positive and based on the sensitivity analysis, it can be concluded that these results are robust. Highlights: Mussel aquaculture is an appealing commercial model for increased returns in offshore wind farms. Offshore mussel aquaculture can use a simple system of long lines and continuous looped droppers. The economic performance withstands considerable changes in cost and revenues. Based on the risk assessment, mitigation strategies are formulated and no high risk remained. A pilot with offshore mussel cultivation is needed to generate practical evidence required.